Translation Analysis on Directive Speech Acts Found in YouTube Video of Vice Indonesia Entitled: Polemik Poligami di Indonesia: Berbagi Surga - Eni Putri Handayani (Universitas Sebelas Maret, 2020)
This research aims to identify the categories of directive speech act contained in the subtitle YouTube Video of VICE Indonesia: Polemik Poligami di Indonesia: Berbagi Surga; to describe the translation technique used in the video and to identify the quality of the directive speech acts translation, in terms of accuracy and acceptability. Two methods of data collection were employed: content analysis used to obtain data from both source and target texts and questionnaire was used to gather data of accuracy, and acceptability. The researcher has found 14 categories of directive speech in the total of 69 data found in the subtitle of the VICE Indonesia’s YouTube video entitled: Polemik Poligami di Indonesia: Berbagi Surga. The result of translation technique analysis shows 13 translation techniques used and a total of 187 times the techniques were applied by the translator in translating the directive speech act. The mean for accuracy is 2.87, means that the subtitle is considered as accurate. While the mean for the is 2.93, means the subtitle also could be considered as acceptable.